2000
DOI: 10.1002/(sici)1097-4644(20000401)77:1<149::aid-jcb15>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone inhibits collagen synthesis and the activity of rat Col1a1 transgenes mainly by a cAMP-mediated pathway in mouse calvariae

Abstract: We examined the effect of parathyroid hormone and various signaling molecules on collagen synthesis and chloramphenicol acetyltransferase activity in cultured transgenic mouse calvariae carrying fusion genes of the rat Col1a1 promoter and the chloramphenicol acetyltransferase reporter. After 48 h of culture, parathyroid hormone, forskolin, dibutyryl cAMP, 8-bromo cAMP, and phorbol myristate acetate inhibited transgene activity, while the calcium ionophore ionomycin had no effect. Pretreatment of calvariae with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 64 publications
(58 reference statements)
1
5
0
1
Order By: Relevance
“…It has been suggested that some biological effects of 1,25(OH) 2 D 3 may be mediated by the protein kinase C (PKC) signaling pathway [74]. We have shown that stimulation of PKC with phorbol myristate acetate inhibits collagen synthesis in fetal rat calvariae [96] and ColCAT3.6 expression in transgenic mouse calvariae [97]. Therefore, 1,25(OH) 2 D 3 activation of the PKC pathway might inhibit Col1a1 expression.…”
Section: Molecular Mechanisms Of Regulationsupporting
confidence: 91%
“…It has been suggested that some biological effects of 1,25(OH) 2 D 3 may be mediated by the protein kinase C (PKC) signaling pathway [74]. We have shown that stimulation of PKC with phorbol myristate acetate inhibits collagen synthesis in fetal rat calvariae [96] and ColCAT3.6 expression in transgenic mouse calvariae [97]. Therefore, 1,25(OH) 2 D 3 activation of the PKC pathway might inhibit Col1a1 expression.…”
Section: Molecular Mechanisms Of Regulationsupporting
confidence: 91%
“…Because the response in calvaria is similar to tibia and femur, the calvaria can be used for analyses examining mechanism of diabetes induced bone loss. This Wnding also supports the multiple reports utilizing calvaria and calvaria derived osteoblasts to examine mechanisms of bone responsiveness to factors such as hormones, stress, and healing (Aronow et al 1990;Bogdanovic et al 2000;Harrison et al 1998;Ikegame et al 2001;Jiang et al 2006;Kream et al 1985;McCauley et al 2001;Woitge and Kream 2000).…”
Section: Controlmentioning
confidence: 99%
“…In contrast, type I collagen and osteonectin genes were well expressed. Although consistent with an earlier study (53), PTH 1-34 treatment alone appeared to moderately inhibit the expression of type I collagen, and Th2 cell condition medium did not exert a strong effect on type I collagen gene expression whether or not PTH was antagonized by PTH (Fig. 7A).…”
Section: Th1 And/or Th2 Cytokine Environment Has Only Minimal Effectsmentioning
confidence: 99%